Respuesta :

Answer:

[tex]f^{-1}(x) = x + 3[/tex]

Step-by-step explanation:

Given the function, f(x) = x - 3:

To find its inverse function:

Replace f(x) with y in the original function.

y = x - 3

Next, switch x and y:

x = y - 3

Add 3 to both sides:

x + 3 = y - 3 + 3

x + 3 = y

Replace y with [tex]f^{-1}(x)[/tex]:

[tex]x + 3 = f^{-1}(x)[/tex]  ← This is the inverse function of f(x) = x-3.

Please mark my answers as the Brainliest, if you find this solution helpful :)

Hope this helps.Have a great day
Ver imagen chayadavei
ACCESS MORE